Pengendalian Proyek dengan Metode Earned Value pada Pekerjaan Rehabilitasi Jaringan Irigasi Sumber Nangka Jember - Eriyanti , Merlita; Kuryanto, Totok Dwi; Gunasti, Amri (Indonesian Journal Publisher, 2024)
The rehabilitation of the D.I Sumber Nangka Irrigation Network takes 180 days or about 6 months to implement, with a budget of Rp. 4,077,964,693. In this study, the authors will analyze the data using the Earned Value method. Therefore, there is no shortage of research on the basic components of project work costs and the realization of completion of work in the field is not too late. The purpose of this research is to calculate the cost of BCWS, BCWP, and ACWP. The results of the D.I Sumber Nangka Irrigation Network Rehabilitation study, Kec. Ledokombo was completed in the 24th week with a total cost of Rp. 4,077,964,693. in the 1st week to the 24th week the fee used is Rp. 3,702,175,554.